2017
DOI: 10.1186/s12967-017-1128-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimized creation of glioblastoma patient derived xenografts for use in preclinical studies

Abstract: BackgroundGlioblastoma multiforme (GBM) is the most common and lethal brain tumor in adults, highlighting the need for novel treatment strategies. Patient derived xenografts (PDX) represent a valuable tool to accomplish this task.MethodsPDX were established by implanting GBM tissue subcutaneously. Engraftment success was compared between NMRI Foxn1nu and NOD/SCID as well as between fresh and cryopreserved tissue. Established PDX were analyzed histologically and molecularly. Five PDX were experimentally treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 28 publications
(28 reference statements)
4
36
0
Order By: Relevance
“…In the present study, we describe the successful engraftment of glioblastoma samples to nude mice, to generate heterotopic PDXs. Other studies reported successful take rates of 22-26% for glioblastoma in nude mice [25,26]. In our study, the subcutaneous heterotopic transplantation of tumour chunks on NMRI nude mice yielded 46% success.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In the present study, we describe the successful engraftment of glioblastoma samples to nude mice, to generate heterotopic PDXs. Other studies reported successful take rates of 22-26% for glioblastoma in nude mice [25,26]. In our study, the subcutaneous heterotopic transplantation of tumour chunks on NMRI nude mice yielded 46% success.…”
Section: Discussionsupporting
confidence: 56%
“…Microsatellite analysis corroborated that the PDXs originated from the transplanted material, although minor changes, such as loss of heterozygosity and imbalance could be observed. Other studies described genetic modifications (e.g., gene amplification, gain/loss of mutation) in early passage PDXs in comparison to the patients' samples [26,43], despite a high similarity. Some changes might be occurring de novo, or they might reflect selection of pre-existing subpopulations during transplantation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cell lines were established from GBM tissue of three different heterotopic patient derived xenograft (PDX) tumors with varying EGFR copy numbers [ 22 ]. All PDX models were established by implanting GBM tissue received from the operation theater at the department of neurosurgery at the university medicine of Rostock subcutaneously into the flanks of immunodeficient NMRI Foxn 1 nu mice [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, substances targeting EGFR or its downstream targets have yet to prove effective in clinical GBM trials [ 19 21 ]. Although genomic EGFR amplification can be well maintained in in vivo models of glioblastoma [ 22 , 23 ], research in a preclinical setting in vitro is hampered by the fact that common cell culture models of GBM lack EGFR gene amplification [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%